2012 IEEE Symposium on Wireless Technology and Applications (ISWTA) 2012
DOI: 10.1109/iswta.2012.6373857
|View full text |Cite
|
Sign up to set email alerts
|

UWB microstrip antenna based on circular patch topology with stepped blocks (wing)

Abstract: This paper presents the design of Ultra Wideband (UWB) microstrip antenna consisting of a circular monopole patch antenna with 3 block stepped (wing). The antenna design is an improvement from previous research and it is simulated using CST Microwave Studio software. This antenna was designed on Rogers 5880 printed circuit board (PCB) with overall size of 26 × 40 × 0.787 mm 3 and dielectric substrate, ε r = 2.2. The performance of the designed antenna was analyzed in term of bandwidth, gain, return loss, radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This antenna design is the improvement from [6]. DGS technique was apply on this antenna in order improved the stable radiation pattern thus decreasinf the size of the antenna.…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This antenna design is the improvement from [6]. DGS technique was apply on this antenna in order improved the stable radiation pattern thus decreasinf the size of the antenna.…”
Section: Antenna Designmentioning
confidence: 99%
“…Previously, the authors have reported on the design of UWB microstrip antenna based on circular patch topology with stepped blocks [6]. This paper achieved improved return loss and constant radiation pattern throughout the UWB frequency,a circular patch microstrip with three blocks, stepped microstrip line antenna design was investigated through simulations in Computer Simulation Technology, CST [10], and actual measurement of the fabricated antenna.The printed microstrip feed structures perform a matching and phase adjustment providing a higher gain with little additional cost.…”
Section: Introductionmentioning
confidence: 99%